2018
DOI: 10.1002/ece3.3835
|View full text |Cite
|
Sign up to set email alerts
|

Testing ontogenetic patterns of sexual size dimorphism against expectations of the expensive tissue hypothesis, an intraspecific example using oyster toadfish (Opsanus tau)

Abstract: Trade‐offs associated with sexual size dimorphism (SSD) are well documented across the Tree of Life. However, studies of SSD often do not consider potential investment trade‐offs between metabolically expensive structures under sexual selection and other morphological modules. Based on the expectations of the expensive tissue hypothesis, investment in one metabolically expensive structure should come at the direct cost of investment in another. Here, we examine allometric trends in the ontogeny of oyster toadf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, other studies have found no such relationship or even the opposite (Lemaître et al, 2009;Barrickman and Lin, 2010;Navarrete et al, 2011;Liu et al, 2018). The study of Opsanus tau shows that increased investment in one structure does not necessarily drive a loss of mass in one or more organs (Dornburg et al, 2018). Studies in mice have shown that evolutionary increase in cognitive abilities was initially associated with brain plasticity and fueled by an enlarged gut, which was not traded off for brain size, as the ETH posits (Konarzewski et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…On the contrary, other studies have found no such relationship or even the opposite (Lemaître et al, 2009;Barrickman and Lin, 2010;Navarrete et al, 2011;Liu et al, 2018). The study of Opsanus tau shows that increased investment in one structure does not necessarily drive a loss of mass in one or more organs (Dornburg et al, 2018). Studies in mice have shown that evolutionary increase in cognitive abilities was initially associated with brain plasticity and fueled by an enlarged gut, which was not traded off for brain size, as the ETH posits (Konarzewski et al, 2020).…”
Section: Introductionmentioning
confidence: 96%